Topical calcineurin inhibitors compromise stratum corneum integrity, epidermal permeability and antimicrobial barrier function - Minjeong Kim; Minyoung Jung; Seung‐Phil Hong; Hyerin Jeon; Minjung Kim; Mee‐Yon Cho; Seung Hun Lee; Mao‐Qiang Man; Peter M. Elias; Eung‐Ho Choi (2009)
Please cite this paper as: Topical calcineurin inhibitors compromise stratum corneum integrity, epidermal permeability and antimicrobial barrier function. Experimental Dermatology 2010; 19: 501–510. Abstract Background: Topical calcineurin inhibitors (TCIs) such as pimecrolimus and tacrolimus have recently been used for dermatologic diseases including atopic dermatitis instead of topical glucocorticoids, because they display comparable efficacy, but less‐frequent side effects. Although even short‐term topical glucocorticoid compromise epidermal permeability barrier homeostasis, the effects of TCI on barrier function have not yet been reported. However, viral infections such as eczema herpeticum and molluscum contagiosum, which could indicate an impaired skin barrier, continue to occur with TCI use in atopic dermatitis. Objectives: We determined here whether TCIs disrupt epidermal permeability barrier and antimicrobial function, and whether these effects can be prevented. Methods and results: In normal humans, topical pimecrolimus and tacrolimus applied twice‐daily for 5 days, delay barrier recovery without an increase in basal transepidermal water loss was observed. Co‐application of physiologic lipid mixture (PLM) containing an equimolar ratio of ceramides, cholesterol and free fatty acids normalized barrier homeostasis in the face of topical TCIs. In hairless mice, 4 days of TCI treatment also disrupted barrier function significantly. TCIs‐treated epidermis showed the decrease of epidermal lipid content, lamellar body number and secretion, and lipid synthesis‐related enzymes such as 3‐hydroxy‐3‐methylglutaryl‐CoA (HMG‐CoA) reductase, serine‐palmitoyl transferase and fatty acid synthase, implying decreased lipid synthesis. TCIs also suppressed expression of IL‐1α and antimicrobial peptides, CRAMP and mouse β‐defensin 3. However, these TCI‐induced abnormalities can be overridden by topical replacement with PLM. Conclusions: Our results demonstrate that TCIs induce negative effects on the skin barrier including permeability and antimicrobial functions, which are mediated by decreasing epidermal lipid synthesis, lamellar body secretion and antimicrobial peptides expression through suppression of cytokine such as IL‐1α, therefore co‐treatment with PLM would be helpful to overcome these negative effects.